2009
DOI: 10.1111/j.1365-313x.2008.03720.x
|View full text |Cite
|
Sign up to set email alerts
|

Live‐cell imaging of viral RNA genomes using a Pumilio‐based reporter

Abstract: SummaryWe describe a method for localizing plant viral RNAs in vivo using Pumilio, an RNA-binding protein, coupled to bimolecular fluorescence complementation (BiFC). Two Pumilio homology domain (PUMHD) polypeptides, fused to either the N-or C-terminal halves of split mCitrine, were engineered to recognize two closely adjacent eight-nucleotide sequences in the genomic RNA of tobacco mosaic virus (TMV). Binding of the PUMHDs to their target sites brought the split mCitrine halves into close proximity, allowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
156
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(173 citation statements)
references
References 73 publications
7
156
0
Order By: Relevance
“…Pumilio-based RNA imaging has enabled subcellular detection of the mRNAs of mitochondrial NADH dehydrogenase and -actin, as well as retroviral RNA in mammalian cultured cells (20)(21)(22)(23), and of the genomes of Tobacco mosaic virus, Potato virus X and Turnip mosaic virus in live plant tissue (24)(25)(26)(27). Of particular relevance to the topic of this volume, Pumilio-based RNA imaging has recently shown that Potato virus X is present in membrane structures at the entrances of plasmodesmata that also contain the viral replicase (27).…”
Section: Rna-binding Domain Of Pumilio Proteinsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pumilio-based RNA imaging has enabled subcellular detection of the mRNAs of mitochondrial NADH dehydrogenase and -actin, as well as retroviral RNA in mammalian cultured cells (20)(21)(22)(23), and of the genomes of Tobacco mosaic virus, Potato virus X and Turnip mosaic virus in live plant tissue (24)(25)(26)(27). Of particular relevance to the topic of this volume, Pumilio-based RNA imaging has recently shown that Potato virus X is present in membrane structures at the entrances of plasmodesmata that also contain the viral replicase (27).…”
Section: Rna-binding Domain Of Pumilio Proteinsmentioning
confidence: 99%
“…The advantages of using modified PUMHDs for RNA imaging are 1) untagged, native RNA species expressed from their native genomic context can be localised (20,21,24), avoiding both the need to modify the RNA and to introduce expression constructs into the genome; 2) if instead PUMHD recognition sequences are engineered into an RNA as a tag, no extensive secondary structures are introduced which might affect RNA function and localisation (though the PUMHD can actually access substantially structured target motifs (18)); 3) PUMHD variants can have 10-to 100-fold higher RNA affinities than stem-loop binding peptides used in alternative RNA imaging systems, thus PUMHD-based imaging is potentially more sensitive.…”
Section: Rna-binding Domain Of Pumilio Proteinsmentioning
confidence: 99%
See 3 more Smart Citations